Water waves scattering by floating rigid dock and breakwaters using improved singular boundary method under regular and irregular waves - Kailash Chand Swami; Santanu Kumar Dash; Santanu Koley (Results in Engineering, 2025)
This study explores the interaction between water waves and a pair of porous trapezoidal-shaped breakwaters of varying sizes kept at a finite distance apart from a floating rigid dock under regular and irregular waves. Several factors are considered, including the friction coefficient and porosity of the breakwater, to understand the phenomena of wave characteristics transformations. The improved singular boundary method (ISBM) handles complex boundary conditions and irregular structural shapes, leading to more accurate predictions and better design efficiency for the present physical model. This ISBM technique does not require singular numerical integration over the elements, and the unknown quantities that are to be determined are expressed as linear combinations of the fundamental solutions and their derivatives at the nodal points. The breakwater's porosity is modeled using the Sollitt and Cross (1972) [1] model, which accounts for the passage of water waves through the thick porous structures. Further, for irregular wave analysis, the Pierson-Moskowitz spectral wave energy density is adopted to represent the fully developed sea states, ensuring realistic wave conditions for offshore applications. The spectral representation of irregular waves is incorporated into the numerical model, facilitating an in-depth inclusion analysis of wave-structure interactions under stochastic sea states. This study concludes that the wave force acting on the dock significantly reduces when the breakwater's structural size increases. Moreover, the wave forces acting on the dock are significantly influenced by the sea state characteristics.